2017
DOI: 10.3329/jbcps.v35i4.34738
|View full text |Cite
|
Sign up to set email alerts
|

Medico-social Profile of Women Experiencing Menopausal Syndrome Attending a Periurban Hospital

Abstract: Women's health is a global concern now a days. Studies on issues relating to menopause is lacking Bangladesh and those been conducted mainly focus on physical and psychological symptoms around the time of menopause. This cross sectional study was done to explore the sociomedical context and nutritional characteristics of a group of women approaching menopause A total 106 women aged 45-60 years attending Gynae outpatient department of a tertiary hospital between MarchMay, 2013 was interviewed using structured q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(5 reference statements)
1
0
0
Order By: Relevance
“…The present study revealed that the average age at menopause among the women in the Geneva camp was 45.38 years which is similar to the ndings of the study of Tasnim et al, (37). However, the mean age of menopause in Bangladesh was reported as 48 to 52 years (28, 38) which is higher than the current study.…”
Section: Discussionsupporting
confidence: 87%
“…The present study revealed that the average age at menopause among the women in the Geneva camp was 45.38 years which is similar to the ndings of the study of Tasnim et al, (37). However, the mean age of menopause in Bangladesh was reported as 48 to 52 years (28, 38) which is higher than the current study.…”
Section: Discussionsupporting
confidence: 87%